Potential of Catalytic Ozonation in Treatment of Industrial Textile Wastewater in Indonesia: Review - Rame Rame; Purwanto Purwanto; Sudarno Sudarno (Jurnal Riset Teknologi Pencegahan Pencemaran Industri, 2020)
Industrial textile wastewater is one of the most heavily polluting in Indonesia. Wastewater from industrial textile contains organic contamination that is very difficult to remove pollutants that remaining even though it has been through the usual wastewater treatment unit installed and bio refractory in nature. Toxic organic compounds discharged from the textile industry, such as colored dyes, heavy metals, and various chemicals, will hurt the environment. These contaminants have been proven toxic to the biotic environment, such as mutagenic, which can increase the incidence of cancer and endocrine disruptor effects. Removal of contaminants from industrial textile wastewater is currently one of the most critical subjects in water pollution prevention. Applications of catalytic ozonation treatment initially, powder catalysts have been employed, and later, the use of activated carbon materials in more advanced catalyst structures reported, and more sophisticated types of catalyst equipment namely carbon nanotube, and nanoparticles. In-depth research on the combination of ozonation and catalytic research of industrial textile wastewater treatment has the potential to become a well-developed approach to treatment industrial textile wastewater. This review provides process principles and characteristics, including the use of various catalysts, variations in reactor design, and application catalytic ozonation in synthetic textile wastewater and real industrial textile wastewater outlined and discussed. Include future research directions of the treatment of industrial textile wastewater in to clean water with drink quality.